Candesartan, an angiotensin-II receptor blocker, ameliorates insulin resistance and hepatosteatosis by reducing intracellular calcium overload and lipid accumulation - Jin Wook Lee; Hyun-Oh Gu; Yunshin Jung; YunJae Jung; Seung-Yong Seo; Jeong-Hee Hong; In-Sun Hong; Dae Ho Lee; Ok-Hee Kim; Byung-Chul Oh (Experimental and Molecular Medicine, 2023)
Abstract Insulin resistance is a major contributor to the pathogenesis of several human diseases, including type 2 diabetes, hypertension, and hyperlipidemia. Notably, insulin resistance and hypertension share common abnormalities, including increased oxidative stress, inflammation, and organelle dysfunction. Recently, we showed that excess intracellular Ca2+, a known pathogenic factor in hypertension, acts as a critical negative regulator of insulin signaling by forming Ca2+-phosphoinositides that prevent the membrane localization of AKT, a key serine/threonine kinase signaling molecule. Whether preventing intracellular Ca2+ overload improves insulin sensitivity, however, has not yet been investigated. Here, we show that the antihypertensive agent candesartan, compared with other angiotensin-II receptor blockers, has previously unrecognized beneficial effects on attenuating insulin resistance. We found that candesartan markedly reduced palmitic acid (PA)-induced intracellular Ca2+ overload and lipid accumulation by normalizing dysregulated store-operated channel (SOC)-mediated Ca2+ entry into cells, which alleviated PA-induced insulin resistance by promoting insulin-stimulated AKT membrane localization and increased the phosphorylation of AKT and its downstream substrates. As pharmacological approaches to attenuate intracellular Ca2+ overload in vivo, administering candesartan to obese mice successfully decreased insulin resistance, hepatic steatosis, dyslipidemia, and tissue inflammation by inhibiting dysregulated SOC-mediated Ca2+ entry and ectopic lipid accumulation. The resulting alterations in the phosphorylation of key signaling molecules consequently alleviate impaired insulin signaling by increasing the postprandial membrane localization and phosphorylation of AKT. Thus, our findings provide robust evidence for the pleiotropic contribution of intracellular Ca2+ overload in the pathogenesis of insulin resistance and suggest that there are viable approved drugs that can be repurposed for the treatment of insulin resistance and hypertension.